L’hybridité cachée de la mise au travail en situation de stage en travail social - Camille Montefusco (Activités)
In sandwich courses, students are faced with hybrid work environments. The aim is to do a job while at the same time learning how to do it. During internships in social work, students are guided by more experienced colleagues and tutors, but they are also required to share activities with patients in institutions without the immediate physical proximity of experienced colleagues. This article seeks to understand how, and under what conditions, “work experiences” can constitute learning opportunities as part of a learning trajectory in social work. Theoretically, the research approach is based on an interactional perspective in work analysis. A detailed analysis of emotional, deontic and epistemic interactions is deployed on the basis of transcripts to show how interactions at work outside the presence of trainers can constitute training resources, particularly for the learning of emotional aspects of work.